New Testing Techniques to Evaluate the Quality of Information Visualization Implementations (LACCEI, 2024)
The use of information visualization has significantly grown thanks to Industry 4.0, and now we can see its usage in more critical sectors. In this context, the implementation of such visualizations must adhere to higher quality standards. To ensure such quality, we present a set of tools developed from a software engineering perspective, particularly from the software verification and validation area. These visualization testing tools go from one to test interactions from the user point of view to another to test their code at run time. Since the toolset is free and open-source, we believe it can be the foundational basis for future developments to expand its functionality and application domains.